Non-commutative vector valued Lp-spaces and completely p-summing maps - Pisier Gilles (Paris Societe Mathematique de France, 1998)
Here is introduced a non-commutative analog of Banach space valued Lp-spaces in the category of operator spaces. Thus, given a von Neumann algebra M equipped with a faithful normal semi-finite trace & an operator space E. There are two important restrict
Keywords: Fourier multipliers; Non-commutative Lp-space; Operator space